Groundwater radon exposure and risk of lung cancer: A population-based study in Finland - Hadkhale, Kishor; Atosuo, Janne; Putus, Tuula (Frontiers in Oncology, 2022)
Naturally occurring radioactive elements can be found in groundwater and exposure to such elements is associated with an increased risk of lung cancer. In this study, we aimed to observe the association between exposure to these radioactive elements in groundwater and the risk of lung cancer in selected regions in Finland. This is a population-based study from 1955 to 2019 in Finland. The exposed municipalities with their corresponding hospital districts were selected based on radon measurements at groundwater treatment plants. Lung cancer cases were obtained from the Finnish cancer registry. The 5-year incidence rates for lung cancer were calculated and a comparison was made between each of the hospital districts with radon exposure. More than 93,000 cases of lung cancer were reported in the radon-exposed regions over the examined period of 64 years. The highest number of cases was recorded in the Helsinki University hospital district and the least in the Southern Savo hospital district. Similarly, the lung cancer incidence rate was highest in Lapland and lowest in the Southern Savo hospital district. The number of daily smokers in the working-age population appears to have decreased in all the hospital districts from 2013 to 2018. A statistically significant increased risk of lung cancer was observed in the high radon-exposed hospital districts compared to those with lower exposure. Groundwater radon exposure is observed to be associated with an increased risk of lung cancer.